Legal Protection and Social Reintegration of Persons with Mental Disabilities in Indonesia - Jagkson, Ignasius Yulianus; Prayuti, Yuyut (LifeSciFi, 2025)
Persons with mental disorders, legally recognized as persons with psychosocial disabilities, are entitled to fundamental constitutional rights, including equal treatment, freedom from discrimination, and a dignified life. However, despite guarantees under Indonesian law and the Convention on the Rights of Persons with Disabilities, the protection mechanism for individuals leaving psychiatric institutional care remains structurally inadequate, resulting in persistent social rejection and family abandonment. This study aims to evaluate the effectiveness of existing legal protections and identify the structural barriers that hinder full social reintegration. Using normative legal research with statutory, conceptual, and case-based approaches, the analysis focuses on Law Number 18 of 2014, Law Number 8 of 2016, and the Convention on the Rights of Persons with Disabilities. Findings indicate that the absence of firm penal sanctions for discriminatory acts, combined with deep-rooted social stigma and insufficient community-based reintegration support, renders current legal safeguards ineffective. The study concludes that comprehensive regulatory reform is needed, emphasizing the inclusion of strict sanctions and mandatory community support systems to ensure the realization of the right to full and dignified reintegration for persons with psychosocial disabilities.